The Team Allocator Game: Allocation Power in Public Goods Games - Alexandros Karakostas; Martin G. Kocher; Dominik Matzat; Holger A. Rau; Gerhard Riewe (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We analyze linear, weakest-link and best-shot public goods games in which a distinguished team member, the team allocator, has property rights over the benefits from the public good and can distribute them among team members. These team allocator games are intended to capture natural asymmetries in hierarchical teams facing social dilemmas, such as those that exist in work teams. Our results show that the introduction of a team allocator leads to pronounced cooperation in both linear and best-shot public-good games, while it has no effect in the weakest-link public good. The team allocator uses her allocation power to distribute benefits from the public good in a way that motivates people to contribute. Re-allocating team payoffs allows the team allocator to reward cooperating team members and to sanction non-cooperating members at no efficiency losses from explicit sanctioning costs. As a result, team profits are higher in the linear team allocator game but not in the best-shot case, where the lack of coordination leads to a welfare decrease for the remaining team members.
Keywords: C72; C91; C92; 330; public goods provision; experiment; institutions; cooperation; allocation power; teams